Implementation of 3D printing as a didactic tool for problem solving of engineering systems and devices - Monroy-Peláez, Ángel Rafael; Juarez-Acosta, Isaac; Miralrio, Alan; Montes de Oca, Saul (Frontiers in Education, 2025)
This study explored the impact of 3D printing as an educational tool for engineering systems and device instruction with students of Tecnologico de Monterrey, Campus Toluca, implemented during the August–December 2023 semester. This initiative was integrated into two courses: Modeling Motion in Engineering and Application of Conservation Laws in Engineering Systems. The same group of students (three experimental groups, 73 students; two control groups, 57 students) participated throughout the study. Experimental groups incorporated 3D printing into their challenge-based learning experience, requiring prototypes developed with this technology. In contrast, control groups utilized traditional methods for prototyping, excluding 3D printing. The study evaluated how this integration affects the quality of students’ proposed solutions and their attitudes toward problem-solving within a challenge-based learning framework. The assessment employed the Attitudes and Approaches to Problem-Solving Survey, with pre-surveys administered at the study’s onset and post-surveys conducted at its conclusion. Results were analyzed to track shifts in problem-solving attitudes over time. This research provides insights into the effectiveness of emerging technologies, such as 3D printing, in fostering innovation and enhancing engineering education, providing a basis for broader application in academic settings.